Purification and optimization of conditions for DNA polymerase isolated from thermophile bacteria Bacillus caldolyticus - Popovski, Zoran T; Nestorovski, Tome; Svetozarevic, Milica; Milevska, Elizabeta Miskoska (Society of Chemists and Technologists of Macedonia, 2017)
Тhermophilic bacteria Bacillus caldolyticus isolated from the hot spring in Bansko, Republic of Macedonia, were used for the isolation of DNA polymerase. Bacterial cells were disrupted by sonication and the first step in the purification of DNA polymerase was 40% ammonium sulfate precipitation. This was followed by chromatographic procedures on Sephadex G-50, DE-52 and CM-52 cellulose. DNA polymerase activity was analyzed at each step of purification using the incorporation of 3H dATP in activated calf thymus DNA. The purity of the DNA polymerase was analyzed on SDS PAGE. Optimal conditions of activity were determined for temperature, pH, dNTP and Mg++ concentration. In addition, the effect of ethanol and EDTA as possible inhibitors of polymerase activity was also analyzed. The optimal temperature of DNA polymerase was 66 ºC; the optimal pH was 7.2, optimal MgCl2 concentration was 2.5 mM, and the optimal substrate concentration was 2.5 × 10–6 M dNTP. The inhibitory effect of EDTA and ethanol on DNA polymerase was above 10 mM and 10%, respectively.
Keywords: Bacillus caldolyticus; DNA polymerase; purification; optimization; inhibitors